Paediatric nurses' satisfaction with organisational communication, job satisfaction, and intention to stay: A structural equation modelling analysis. Issue 4 (August 2021) - Doleman, Gemma; Twigg, Di; Bayes, Sara; Chivers, Paola
Abstract: Aims: To examine the effect of paediatric nurses' organisational communication satisfaction on job satisfaction and intention to stay in their role. Background: Nurses' satisfaction with organisational communication has not been studied in-depth in recent years and specifically, there is a paucity of evidence in relation to paediatric nurses' job satisfaction and intention to stay in their current job. Methods: A cross-sectional quantitative research design using questionnaires was used. Descriptive statistics were used to analyse demographic data and structural equation modelling was used to analyse the hypothesised models. Findings: The constructs of supervisor relationships, communication climate and media quality had a significant direct effect on paediatric nurses' job satisfaction. Job satisfaction was found to have a significant negative inverse relationship with intention to leave and looking for another job in nursing. Conclusion: Strategies that promote job satisfaction and communication satisfaction should be disseminated by management in order to reduce paediatric nurse intention to leave and looking for another job. Implications for nursing management: The study highlighted the need for improvement in the efficacy of communication systems for upward and downward feedback in order to improve supervisor subordinate relationship. Further, managers need to facilitate adequate infiltration of relevant information to maintain low levels of frustration and prevent development of grapevines amongst nurses.